Carbene‐Catalyzed Three‐Component Cascade Reaction of Benzofuran‐2‐ones and Enals: Construction of Spirobenzofuranone‐δ‐lactones. Issue 12 (7th October 2021) - Wang, Zhan‐Yong; Shen, Fumin; Yang, Ting; Zhang, Jun‐Kai; Chen, Rongxiang; Wang, Kai‐Kai; Liu, Hongxin
Abstract: A convenient method was developed via an NHC mediated three‐component cascade reaction for the construction of medicinally important spirobenzofuranone derivatives. The reaction features mild reaction conditions and generates three consecutive stereocenters, one of which is an all‐carbon substitution. The protocol can accommodate various substituents and substitution patterns, afford the products in moderate to good yields with excellent diastereoselectivities and moderate enantioselectivity. Abstract : An NHC‐catalyzed reaction with benzofuran‐2‐one type compounds as the starting materials for the synthesis of medicinally important spirobenzofuranone derivatives with four new bonds, three consecutive stereocenters and one all‐carbon quaternary carbon is reported.